The Enhanced Expression of Cruzipain-Like Molecules in the Phytoflagellate Phytomonas serpens Recovered From the Invertebrate and Plant Hosts - Oliveira, Simone S. C.; Elias, Camila G. R.; Dias, Felipe A.; Lopes, Angela H.; d’Avila-Levy, Claudia M.; Santos, André L. S.; Branquinha, Marta H. (Frontiers in Cellular and Infection Microbiology, 2022)
Phytomonas serpens is a protozoan parasite that alternates its life cycle between two hosts: an invertebrate vector and the tomato fruit. This phytoflagellate is able to synthesize proteins displaying similarity to the cysteine peptidase named cruzipain, an important virulence factor from Trypanosoma cruzi, the etiologic agent of Chagas disease. Herein, the growth of P. serpens in complex medium (BHI) supplemented with natural tomato extract (NTE) resulted in the increased expression of cysteine peptidases, as verified by the hydrolysis of the fluorogenic substrate Z-Phe-Arg-AMC and by gelatin-SDS-PAGE. Phytoflagellates showed no changes in morphology, morphometry and viability, but the proliferation was slightly reduced when cultivated in the presence of NTE. The enhanced proteolytic activity was accompanied by a significant increase in the expression of cruzipain-like molecules, as verified by flow cytometry using anti-cruzipain antibodies. In parallel, parasites incubated under chemically defined conditions (PBS supplemented with glucose) and added of different concentration of NTE revealed an augmentation in the production of cruzipain-like molecules in a typically dose-dependent way. Similarly, P. serpens recovered from the infection of mature tomatoes showed an increase in the expression of molecules homologous to cruzipain; however, cells showed a smaller size compared to parasites grown in BHI medium. Furthermore, phytoflagellates incubated with dissected salivary glands from Oncopeltus fasciatus or recovered from the hemolymph of infected insects also showed a strong enhance in the expression of cruzipain-like molecules that is more relevant in the hemolymph. Collectively, our results showed that cysteine peptidases displaying similarities to cruzipain are more expressed during the life cycle of the phytoflagellate P. serpens both in the invertebrate and plant hosts.